2015
DOI: 10.1097/j.pain.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Are migraine and tension-type headache diagnostic types or points on a severity continuum? An exploration of the latent taxometric structure of headache

Abstract: The objective of this study was to assess whether migraine and tension-type headache (TTH) are best viewed as discrete entities or points on a severity continuum using taxometric analysis. Historically, classification systems have conceptualized the primary headache disorders of migraine and TTH as fundamentally different disorders that are differentiated by their characteristic symptom profiles and, as such, imply differing pathophysiologies and required treatments. Despite this categorical nosology, findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Pediatric data supports the notion that childhood headaches are a continuum, rather than discrete entities [46,47]. Recent findings [48] suggest that “migraine” and “tension-type” headaches might not be separate diagnostic/disease entities, but rather represent a severity continuum for young adults 18–24 years of age who experience chronic headaches more than 3–4 days per week. Two cross-sectional studies [48] with more than 3400 headache patients revealed that those who are experiencing headaches at a younger age (18–24 years old) and with higher frequency (more than 15 headache days/month) displayed a unimodal distribution, suggesting the dimensional construct of a primary headache.…”
Section: Pain Manifestations and Locations Of A Primary Pain Disordersupporting
confidence: 54%
See 1 more Smart Citation
“…Pediatric data supports the notion that childhood headaches are a continuum, rather than discrete entities [46,47]. Recent findings [48] suggest that “migraine” and “tension-type” headaches might not be separate diagnostic/disease entities, but rather represent a severity continuum for young adults 18–24 years of age who experience chronic headaches more than 3–4 days per week. Two cross-sectional studies [48] with more than 3400 headache patients revealed that those who are experiencing headaches at a younger age (18–24 years old) and with higher frequency (more than 15 headache days/month) displayed a unimodal distribution, suggesting the dimensional construct of a primary headache.…”
Section: Pain Manifestations and Locations Of A Primary Pain Disordersupporting
confidence: 54%
“…Recent findings [48] suggest that “migraine” and “tension-type” headaches might not be separate diagnostic/disease entities, but rather represent a severity continuum for young adults 18–24 years of age who experience chronic headaches more than 3–4 days per week. Two cross-sectional studies [48] with more than 3400 headache patients revealed that those who are experiencing headaches at a younger age (18–24 years old) and with higher frequency (more than 15 headache days/month) displayed a unimodal distribution, suggesting the dimensional construct of a primary headache. Conversely, patients who experienced a lower frequency of headaches and were of older age showed bimodal headache distributions, which could be differentiated into “migraine” versus “tension-type” headache.…”
Section: Pain Manifestations and Locations Of A Primary Pain Disordermentioning
confidence: 99%
“…Diagnostic distinction between these two common headache types is not readily apparent in patients with chronic headaches and of young age. 28 To our knowledge, this is the first study demonstrating that patients with TTH show some visual field deficits like migraineurs. In our study, field loss was 44% and 36% in migraineurs and TTH patients, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Turner et al showed in their taxometric analysis study that diagnostic/symptomatic distinctions between headache types would be less prominent among individuals with frequent headaches and those of younger age. 28 Migraine and TTH are differentiated by their characteristic symptoms and as such imply differing pathophysiologies and required treatments. Despite this categorical nosology, findings continue to emerge suggesting that migraine and TTH instead reflect dimensions of severity within the same headache construct.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were young adults at a southeastern university who participated voluntarily in exchange for modest course credit. As part of an ongoing data collection effort, from August 2012 to December 2013 they completed an online battery of measures, including a computer‐administered structured diagnostic interview for headache. Those meeting ICHD‐3 beta criteria for EM (with or without aura) or chronic migraine comprised the migraine group.…”
Section: Methodsmentioning
confidence: 99%